Antiphase synchrony increases perceived entitativity and uniqueness: A joint hand-clapping task - Fujiwara, Ken; Nomura, Kunihiko; Eto, Miki (Frontiers in Psychology, 2023)
In- and anti-phase are the dominant patterns identified in the study of synchrony in relative phases. Many previous studies have focused on in-phase synchrony and compared it to asynchrony, but antiphase synchrony has yet not been the subject of much research attention. The limited findings on antiphase synchrony suggest that its role or nature is unclear or unstable in human interaction. To account for this factor, this study examined the possibility that antiphase synchrony simultaneously induced perceived entitativity and uniqueness. The results of an experiment employing a joint hand-clapping task supported this prediction. Further, the elevated feeling of uniqueness in those who experienced antiphase synchrony may have increased the self-other overlap for those who felt oneness with their partner, but it decreased overlap for those who did not. The theoretical implications for synchrony literature are discussed.